Studies on visualisation in science classrooms: a systematic literature review. Issue 17 (22nd November 2022) - Kim, Mijung; Jin, Qingna
ABSTRACT: Visualisation has been a critical means of scientific reasoning, knowledge development, and communication. In science classrooms, visualisation plays significant roles for teaching and learning. To better understand the landscape of the existing research on visualisation for supporting student science learning in K to 12 classroom contexts, we undertook a systematic review to investigate what research areas and contexts of visualisation have been examined by science educators and researchers. In particular, this review explored the domains of science subject areas, authors, types and purposes of visualisation in science education research published in peer-reviewed journals between 2011 and 2021 and indexed in the ERIC and Academic Search Complete databases. Our systematic search and subsequent screening process yielded 33 studies for analysis. The findings suggest (a) research on visualisation for student science learning spans across the main science domains (i.e. life science, physical science, chemistry, earth and space science), and grade levels (from Grades 1−12); (b) compared with students' visualisation in social interactive contexts, more studies focused on individual students' visualisation; and (c) the majority of the research focused on students' concept learning through visualisation, rather than visualisation for scientific reasoning and communication. Based on these findings, suggestions for further research are discussed.